Ментальные предпосылки украинского парадокса - Храмова, В.Л. (Наука та наукознавство, 2007)
Определяются господствующие ментальные установки мировосприятия и миропонимания украинцев, их влияние на исторические судьбы народа, охарактеризованы специфика формирования украинской психики, ее архетипы. С этих позиций анализируется Оранжевая революция наших дней, сопоставляется ментальность украинцев и россиян. Показаны культура Киева как своеобразный и в своей целостности еще не изученный феномен, общие для украинцев и россиян философские и литературные традиции, в частности на примере Н.Бердяева и Н.Гоголя, значение русского языка для украинцев как пути в духовную культуру человечества. Визначено пануючі ментальні установки світосприйняття й світогляду українців, їх вплив на історичну долю народу, схарактеризовано специфіку формування української психіки, її архетипи. З цих позицій аналізується Померанчева революція наших днів, співставляється ментальність українців і росіян. Показано культуру Києва як своєрідний й у своїй цілісності ще не досліджений феномен, спільні для українців і росіян філософські та літературні традиції, зокрема на прикладі М.Бердяєва і М.Гоголя, значення російської мови для українців як шляху в духовну культуру людства. The author identifies the prevailing mental purposes of the world perception and world outlook of Ukrainians, their influence on the historical fate of the nation, and describes specifics of fostering the Ukrainian psycho and its archetypes. The Orange Revolution is analyzed in this light, and mentality of Ukrainians and Russians is compared. The culture of Kiev is shown as a unique phenomenon not investigated comprehensively yet; philosophic and literary traditions that are common for Ukrainians and Russians are shown by the example of M.Berdyayev and M.Gogol’; importance of the Russian language for Ukrainians are shown as a means for their integration with the spiritual culture of the humanity.